Thermochromism of CuI Tetrakisguanidine Complexes: Reversible Activation of Metal‐to‐Ligand Charge‐Transfer Bands. Issue 46 (29th September 2015) - Wiesner, Sven; Wagner, Arne; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract: Tetranuclear, intensely blue‐coloured Cu I complexes were synthesised in which two Cu2 X3 − units (X=Br or I) are bridged by a dicationic GFA (guanidino‐functionalised aromatic) ligand. The UV/Vis spectra show a large metal‐to‐ligand charge‐transfer (MLCT) band around 638 nm. The tetranuclear "low‐temperature" complexes are in a temperature‐dependent equilibrium with dinuclear Cu I "high‐temperature" complexes, which result from the reversible elimination of two CuX groups. A massive thermochromism effect results from the extinction of the strong MLCT band upon CuX elimination with increasing temperature. For all complexes, quantum chemical calculations predict a small and method‐dependent energy difference between the possible electronic structures, namely Cu I and dicationic GFA ligand (closed‐shell singlet) versus Cu II and neutral GFA ligand (triplet or broken‐symmetry state). The closed‐shell singlet state is disfavoured by hybrid‐DFT functionals, which mix in exact Hartree–Fock exchange, and is favoured by larger basis sets and consideration of a polar medium. Abstract : Colorful copper : A massive charge‐transfer band is switched on by CuX (X=Br, I) addition to a dinuclear Cu I complex with bridging dicationic tetrakisguanidine ligands.